CZYNNIKI TRANSFORMACJI SYSTEMU POLITYCZNEGO I GOSPODARCZEGO BYŁYCH PAŃSTW KOMUNISTYCZNYCH - Gronkiewicz-Waltz, Hanna (Wydział Prawa i Administracji UAM, 2004)
The paper presents the factors affecting political and economic transition in post-communist countries. The political indicators are: elections with even chances for the opposition in the media during the campaign; rule of law; human rights protection; freedom of the media; protection of property rights and level of corruption. The economic indicators show the level of reform in four sections of the economy - market and trade, enterprise, infrastructure, and financial institutions. The assessment concerns legal regulation: for instance, corporate governance, privatization and liberalization of markets. The overall evaluation leads to the conclusion that there are significant differences in the level of transition among the new members of the EU, the CIS countries and former Yugoslavian countries. The most advanced countries in terms of economic reform are those which also meet a high standard of democracy. The enlargement which took place on 1 May 2004 should have a positive impact on those countries in which the reform process has either stopped or slowed down.
POLITICAL AND ECONOMIC FACTORS OF TRANSITION IN POST-COMMUNIST COUNTRIES